Development of a Practical Learning Module to Enhance Automotive AC Maintenance Competency in Vocational High Schools - Azzaky, Marham Ab Lathif; Wijaya, Burhan Rubai; Hudallah, Noor (Jurnal Penelitian Pendidikan, 2025)
This study aims to enhance the competency of vocational high school students in automotive air conditioning (AC) maintenance by developing a practical learning module. Conducted at SMK Al Asror Semarang, this research utilized the ADDIE development model, encompassing Analysis, Design, Development, Implementation, and Evaluation phases. The analysis identified inadequate facilities and infrastructure as significant factors contributing to students’ low achievement levels. To address this issue, a practical learning module was designed based on the Indonesian National Work Competency Standards (SKKNI) and validated by subject matter and media experts. The implementation involved 29 students who participated in both pre- and post-competency assessments. The module’s practicality was also evaluated in terms of usability, clarity, relevance, and instructional design. In the final stage, students underwent a practical AC maintenance test assessed by external industry professionals. The results demonstrated a substantial improvement in students’ competencies, indicating that the developed module is not only effective but also a valuable instructional resource for enhancing HVACR learning outcomes in vocational education settings.